CC chemokine ligand 2 (CCL2) enhances TTX-sensitive sodium channel activity of primary afferent neurons in the complete Freud adjuvant-induced inflammatory pain model. (19th October 2018) - Luo, Ping; Shao, Jiayun; Jiao, Yingfu; Yu, Weifeng; Rong, Weifang
Abstract: CC chemokine ligand 2 (CCL2) has been implicated in pathological pain, but the mechanism underlying the pronociceptive effect of CCL2 is not fully understood. Voltage-gated sodium (Nav) channels are important determinants of the excitability of sensory neurons. Hence we tested the hypothesis that CCL2 contributes to inflammatory pain via modulating Nav channel activity of primary afferent neurons. Chronic inflammatory pain was induced in rats by intraplantar injection of the complete Freud adjuvant (CFA) to one of the hind paws. Control rats received intraplantar injection of equal volume of saline. A significant increase of CCL2 mRNA and CCL2 receptor (CCR2) protein expression was detected in the ipsilateral dorsal root ganglion (DRG) in CFA-treated rats. Intraplantar injection of CCL2 protein in the control rats had minimal effect on the paw withdrawal threshold (PWT) in response to mechanical stimulation. However, in CFA-treated rats, intraplantar CCL2 led to an increase in pain responses. Patch-clamp recording of acutely dissociated DRG neurons revealed that CCL2 had minimum effect on the excitability of sensory neurons from control rats. However, CCL2 directly depolarized a large proportion of small to medium-sized sensory neurons from CFA-treated rats. In addition, CCL2 was found to enhance whole-cell TTX-sensitive sodium currents without significantly affecting the TTX-resistant sodium currents and the potassium currents. These results are in agreement with previous reports concerning the involvement of CCL2–CCR2 signaling in inflammatory hyperalgesia and further indicate that enhanced TTX-sensitive channel activity may partly underlie the pronociceptive effects of CCL2.